Transcriptional Proposition for Uniquely Developed Protocorm Flowering in Three Orchid Species: Resources for Innovative Breeding - Ahmad, Sagheer; Chen, Jinliao; Chen, Guizhen; Huang, Jie; Hao, Yang; Shi, Xiaoling; Liu, Yuying; Tu, Song; Zhou, Yuzhen; Zhao, Kai; Lan, Siren; Liu, Zhongjian; et al. (Frontiers in Plant Science, 2022)
During orchid seed culture, seeds germinate as protocorms, and protocorms normally develop into plant with leaves and roots. Orchids require many years of vegetative development for flowering. However, under a certain combination of growth cultures, we observed that protocorms can directly flower without leaves and roots. Therefore, we performed comparative transcriptome analysis to identify the different transcriptional regulators of two types of protocorms of Cymbidium ensifolium, Cymbidium sinense, and Cymbidium goeringii. Zinc finger, MYB, AP2, and bHLH were the most abundant transcription factor (TF) families in the transcriptome. Weighted gene coexpression network analysis (WGCNA) was performed to identify hub genes related to leaf and flower development. The key hubs included SPL6, SVP, SEP2, KNOX1, AP2, OFP1, COL12, MYB13, MYB36, MYB59, bHLH086, and ARF7. The hub genes were further validated through statistical tools to propose the roles of key TFs. Therefore, this study initiates to answer that why there is no leaf initiation and root development and how can protocorm bypass the vegetative phase to flower? The outcomes can direct future research on short-span flowering in orchids through protocorms.